2018
DOI: 10.1200/jco.2017.75.2717
|View full text |Cite
|
Sign up to set email alerts
|

Local Control of Soft Tissue and Bone Sarcomas

Abstract: Sarcomas of soft tissue and bone are mesenchymal malignancies that can arise in any anatomic location, most commonly the extremity, retroperitoneum, and trunk. Even for lower grade histologic subtypes, local recurrence can cause significant morbidity and even disease-related death. Although surgery remains the cornerstone of local control, perioperative radiation and systemic therapy are often important adjuvants. This review will summarize the current therapeutic approaches for local control of soft tissue an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 75 publications
1
36
0
Order By: Relevance
“…With the implementation of functional imaging, FDG-PET is highly accurate in detecting both primary and metastatic lesions of STS (2,8,30). In our cohort, PET was used in 12 patients and the initial SUV value seemed to predict the PFS (p=0.04), supporting the development of PET-adaptive treatment strategies.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…With the implementation of functional imaging, FDG-PET is highly accurate in detecting both primary and metastatic lesions of STS (2,8,30). In our cohort, PET was used in 12 patients and the initial SUV value seemed to predict the PFS (p=0.04), supporting the development of PET-adaptive treatment strategies.…”
Section: Discussionsupporting
confidence: 55%
“…In a recent review, Crompton et al reported that surgery and RT are the most important factors for local disease control (8), although other therapeutic options may also have local influence. Gustafson et al indicated that patients should be treated in a specialized Sarcoma Center, and further reported a 2.4-fold higher risk of LRR in patients who were not treated at such a facility (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] However, multiple side effects exist after amputation, limb‐sparing procedure, and high‐dose chemotherapy, such as severe cardiac toxicity and poor life quality. [ 7–10 ] The delicate biomaterials constructed with releasable chemotherapeutic agents are of great priority to be designed for the reconstruction of bone defects and removal of recalcitrant tumors. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…The bone and soft tissue sarcomas most frequently originate in extremities. [ 6 , 7 ] Because they tend to be very invasive, they may extend into the boundary compartments and invade the neurovascular bundle. Nowadays, the tumor can be eradicated either by amputation or limb-salvage surgery.…”
Section: Introductionmentioning
confidence: 99%